Comportamiento organizacional de la cooperativa de trasporte Puebloviejo - Orozco Lascano, Walter Emanuel (2017)
At the beginning the Transport Cooperative "Puebloviejo" served in units called rancheras to various communities in the cantons of Puebloviejo, Ventanas and Urdaneta; in many cases the access roads to these towns were in rustic roads, that is to say, in roadways weighed in some cases and in others were only open trails without having put ballast. With the passage of time some of these routes have been improving and therefore also the service of buses that provide transportation of passengers and cargo